Experimental evaluation of multiple retransmission schemes in IEEE 802.15.4 wireless sensor networks - Odilson T. Valle (2012)
One of the motivations for use of wireless sensor networks (WSNs) in industrial environments is related to the reduced deployment and maintenance costs, when compared to the use of wired networks for connecting single I/O points. Nevertheless, a well-known problem for the use of wireless communication in industrial environments is related to the unreliable nature of the communication medium. Therefore, the search for communication reliability in WSNs is a relevant topic of research for the scientific community. In this paper we propose an innovative message retransmission scheme, based on network coding techniques, to increase the reliability of message exchanges in industrial environments. The proposed technique: NetCod, that improve the probability of message deliver by allowing the message retransmission whenever a loss occurs is experimentally compared with state of the art techniques: BlockACK, Redundant TDMA and Master/Slave. A comparative experimental assessment of these four techniques was performed using MicaZ motes. Metrics such as: message loss, message transmission delay and power consumption were used to comparatively assess the behavior of these retransmission techniques. Â(c) 2012 IEEE.